Elucidation of the Reaction Behavior of Silicon Negative Electrodes in a Bis(fluorosulfonyl)amide‐Based Ionic Liquid Electrolyte. Issue 12 (13th October 2017) - Yamaguchi, Kazuki; Domi, Yasuhiro; Usui, Hiroyuki; Sakaguchi, Hiroki
Abstract: Excellent cycling performance of an electrode composed of silicon alone was achieved in a bis(fluorosulfonyl)amide (FSA)‐based electrolyte, with a high discharge capacity of 950 mA h g −1 observed even at the 500th cycle. To elucidate the reaction behavior of the Si electrode in an FSA‐based ionic liquid electrolyte, we investigated the change in the cross‐sectional morphology of the Si‐active material layer, the distribution of Li in the layer, and the crystallinity of Si on the electrode surface. By cross‐sectional scanning electron microscopy, we confirmed that the electrode thickness increased with the cycle number. The increase in thickness was less noticeable in the FSA‐based electrolyte than in an organic electrolyte. An elemental analysis of the electrode material revealed that a film derived from the electrolyte was formed not only on the surface but also inside of the electrode. Soft X‐ray emission spectroscopy demonstrated that the distribution of Li in the FSA‐based electrolyte was more uniform for the cross‐section of the cycled electrode compared to that in an organic electrolyte. The results of Raman spectroscopy indicated that domains of amorphous Si were homogeneously distributed on the electrode surface in the FSA‐based electrolyte. The uniform distribution of the lithiation−delithiation reaction should help to suppress disintegration of the active material layer. Abstract : Si goes it alone : The thickness of an electrode composed of Si alone was found to increase with the cycle number, with the increase in thickness less noticeable in an bis(fluorosulfonyl)amide (FSA)‐based electrolyte than in an organic electrolyte. Li−K emission was observed at all SXES measured points, which means that the lithiation reaction proceeded uniformly in the Si layer.